2022
DOI: 10.3389/fbioe.2022.1002276
|View full text |Cite
|
Sign up to set email alerts
|

Spinal stability analysis of lumbar interbody fusion according to pelvic type and cage angle based on simplified spinal model with various pelvic indices

Abstract: Recently, the objectives of lumbar interbody fusion (LIF) have been extended to include the correction of broader/relative indications in addition to spinal fixation. Accordingly, LIF must be optimized for sagittal alignment while simultaneously achieving decompression. Therefore, a representative model classified into three pelvic types, i.e., neutral pelvis (NP), anterior pelvis (AP), and retroverted pelvis (RP), was selected according to the pelvic index, and LIF was performed on each representative model t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Recently, a significant increase in the use of computational biomechanics techniques to model and simulate the spine ( Fujiwara et al, 2000 ; Du et al, 2016 ; Wang et al, 2018 ; Wang et al, 2019 ; Song et al, 2021 ; Kim et al, 2022 ; Sim et al, 2022 ) have been reported. Studies focusing on the lumbar facet joints have also been conducted with increasing frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a significant increase in the use of computational biomechanics techniques to model and simulate the spine ( Fujiwara et al, 2000 ; Du et al, 2016 ; Wang et al, 2018 ; Wang et al, 2019 ; Song et al, 2021 ; Kim et al, 2022 ; Sim et al, 2022 ) have been reported. Studies focusing on the lumbar facet joints have also been conducted with increasing frequency.…”
Section: Introductionmentioning
confidence: 99%